Решить систему:[latex] \left \{ {{ \frac{x+y}{x-y}+6 \frac{x-y}{x+y} =5 } \atop { 5y^{2} - x^{2} =1 }} \right. [/latex]

Решить систему: [latex] \left \{ {{ \frac{x+y}{x-y}+6 \frac{x-y}{x+y} =5 } \atop { 5y^{2} - x^{2} =1 }} \right. [/latex]
Гость
Ответ(ы) на вопрос:
Гость
замена: (x+y)/(x-y)=t t+6/t=5 t^2-5t+6=0 t1=2 t2=3 1) (x+y)/(x-y)=2 x+y=2x-2y x=3y 5y^2-9y^2=1 -4y^2=1  нет решений. 2)(x+y)/(x-y)=3    x+y=3x-3y 2x=4y x=2y 5y^2-4y^2=1 y^2=1 y=+-1 x=+-2 Ответ: (2,1);(-2;-1)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы